2016
DOI: 10.1016/j.biopsych.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intrinsic Functional Brain Architecture in Children at Familial Risk of Major Depression

Abstract: Background Neuroimaging studies of patients with major depression have revealed abnormal intrinsic functional connectivity measured during the resting state in multiple, distributed networks. However, it is unclear whether these findings reflect the state of major depression or reflect trait neurobiological underpinnings of risk for major depression. Methods We compared resting-state functional connectivity, measured with functional magnetic resonance imaging (fMRI), between unaffected children of parents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 72 publications
8
50
1
Order By: Relevance
“…These studies provide evidence for premorbid abnormalities in ACC connectivity among high-risk youth, including greater connectivity between the the sgACC and the default mode network, reduced connectivity between the sgACC and the dlPFC (Chai et al, 2015), as well as decreased resting-state connectivity between the dACC and the rostral inferior frontal gyrus relative to those with no family history of depression (Clasen et al, 2014). …”
Section: Acc Connectivity and Adolescent Depressionmentioning
confidence: 93%
“…These studies provide evidence for premorbid abnormalities in ACC connectivity among high-risk youth, including greater connectivity between the the sgACC and the default mode network, reduced connectivity between the sgACC and the dlPFC (Chai et al, 2015), as well as decreased resting-state connectivity between the dACC and the rostral inferior frontal gyrus relative to those with no family history of depression (Clasen et al, 2014). …”
Section: Acc Connectivity and Adolescent Depressionmentioning
confidence: 93%
“…In the baseline wave of the present study (Chai et al, 2015(Chai et al, , 2016, we used fMRI and structural scans to examine function and structure in unaffected children ages 8-14 at familial risk for MDD (high-risk group) and comparison children who were offspring of parents with no lifetime history of any mood disorder (low-risk group). We found that children at high risk for depression had increased connectivity between the DMN and sgACC, and decreased connectivity in CCN regions including the dlPFC (Chai et al, 2016; See Figure 1). In addition, these youth had increased activation to fearful faces in the amygdala and several cortical regions and decreased activation to happy faces in the anterior cingulate cortex and supramarginal gyrus (Chai et al, 2015; See Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the offspring we examined were unaffected with depression, it is unclear whether the differences we observed represented risk factors for the onset of depression, or alternatively, resilience factors associated with protection from depression. Therefore, the current study aimed to examine whether the differences in brain activation, resting-state connectivity and structural differences we observed previously (Chai et al, 2015;Chai et al, 2016) would prospectively predict depression in two ways: That is, we utilized only the a priori neural changes that differentiated the high-versus low-risk children to predict who would exhibit increased depressive symptoms or the onset of depression over time. First, we examined whether the children had emerged with a full episode of MDD during the interval since the baseline scan, using diagnostic interviews covering diagnoses during the interval.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively less is known about functional and effective connectivity of OFC in adult depression, with studies showing greater connectivity of OFC with insula (30), amygdala (31), and a distributed network including prefrontal and cingulate cortices (32), and this enhanced connectivity is associated with more severe depression symptoms (30, 32). Despite prefrontal maturation during adolescence (33), adolescents and adults with and at risk for MDD show a similar pattern of prefrontal resting-state connectivity (34, 35). However, it is unclear whether attenuated OFC activity and/or enhanced OFC connectivity during rewards and losses represents a premorbid risk that precedes the onset of symptoms or is the result of depression onset or treatment exposure, indicating a need for longitudinal research on OFC functioning prior to depression onset.…”
Section: Introductionmentioning
confidence: 99%